Effectiveness of psychosocial school interventions in Finnish schools for refugee and immigrant children, "Refugees Well School" in Finland (RWS-FI): a protocol for a cluster randomized controlled trial - Kankaanpää Reeta; Aalto Sanni; Vänskä Mervi; Lepistö Riina; Punamäki-Gitai Raija-Leena; Soye Emma; Watters Charles; Andersen Arnfinn; Hilden Per Kristian; Derlyun Ilse; Verelst An; Peltonen Kirsi (BMC, 2025)
Background: Schools are natural environments in which to enhance young people's social and emotional skills, mental health, and contact between diverse groups, including students from refugee and immigrant backgrounds. A layered or tiered provision of services is recommended as it can be effective to meet the needs of war-affected adolescents who variably show mental health problems (such as posttraumatic stress disorder (PTSD)). The current protocol describes the study design for a multi-layered intervention model. The study will test the effectiveness of two interventions: a teacher-training intervention In-Service Teacher Training (INSETT) combined with targeted cognitive-behavioral treatment-based Teaching Recovery Techniques (TRT) and a classroom-focused preventive intervention Peer Integration and Enhancement Resources (PIER). We analyze, first, whether the interventions are effective in decreasing psychological distress and increasing positive resources, i.e., prosocial behavior and resilience among refugee and immigrant students. Second, we analyze which student-, school-, and parent-related factors mediate the possible beneficial changes. Third, we look at which groups the interventions are most beneficial to.Methods: A three-arm cluster RCT with parallel assignment, with a 1:1:1 allocation ratio, is applied in 16 schools that agreed to participate in the Refugees Well School interventions and effectiveness study. Schools were randomized to three conditions of two active interventions and a waiting list control condition. Students, their parents, and teachers in intervention and control schools participated in the study at baseline before the interventions, after the interventions, and at 6 to 12 months after the interventions. The primary effectiveness criterion variables are psychological distress (SDQ) symptoms, resilience (CYRM-12), and prosocial behavior (SDQ).Discussion: The current study presents a recommended universal approach of layered interventions aiming to reduce psychological distress and increase resilience among refugee and immigrant students. A combination of promotive, preventive, and targeted interventions may offer a holistic, ecological intervention package for schools to better address the needs of the whole group.